Uso e ocupação do solo no processo de assoreamento do Lago Municipal de Cascavel – PR. - Francisquini, Mateus (2022)
The most relevant impacts of anthropic actions can be seen in a river basin, whether due to agricultural land farming or urbanization. The indiscriminate use of the soil has caused several impacts in river basins, since, it has affected the general dynamics of the hydrological cycle, wherefore, has caused water pollution and sediments production. Sediments have been widely used as environmental indicators, as they have a wide potential to incorporate and accumulate contaminating elements from punctual and diffuse pollution. Sediment traps are, generally, simple instruments that can be applied for many purposes. Thus, this trial aimed at evaluating the influence of soil use and occupation in basins that have helped on drainage and silting of a lake, as well as proposing mitigation measures to improve it. Three collection points were established for sediment trap deposit. The sediment traps remained fourteen days in two collection periods, dry and rainy season. The mapping of soil use over time has shown that the forest did not follow the urban area development. A bathymetric survey was also carried out on the studied lake, which showed a decrease in the volume of water since its construction. Chemical analyses revealed that this reservoir lake shows a disturbance of nutrients coming from outside during the rainy season, a problem that can be associated to the storm sewer system. The geoaccumulation index revealed that metals such as cadmium (Cd) and zinc (Zn) fit into Class 1 in both seasons, while the other studied elements (manganese (Mn), lead (Pb) and copper (Cu)) did not show potential ecological risks. The prevention of production and transport of sediments can only be carried out by integrated actions with a cumulative effect throughout the city.